Facilitating 'reasonable hope' with refugees and asylum seekers - Turner, G (Refugee Studies Centre, University of Oxford, 2017)
The loss of hope over time has led to despair and a mental health crisis for refugees and asylum seekers on Manus Island and Nauru. The use of the principle of ‘reasonable hope’, however, can support their mental health and well-being.